Linear Psoriasis- A rare case report (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Linear psoriasis is a rare form of disease which is very difficult to differentiate from inflammatory linear verrucous epidermal nevus. Sometimes clinical history, physical examination and histopathology analysis may not be sufficient to confirm the diagnosis. We report a case of25 year-old male presented with a linear plaque covered with silvery scales on left upper extremity extending from tip of the index to mid forearm for last 2 years. A skin biopsy was consistent with psoriasis, and the unilateral distribution in a linear pattern led to a diagnosis of linear psoriasis, which is a rare variant of psoriasis. Although histopathologically it can be difficult to distinguish from inflammatory linear verrucous epidermal nevus (ILVEN), linear psoriasis presents in adulthood and responds to conventional topical antipsoriatic therapies.